2017
DOI: 10.1002/adem.201700354
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Control Enabled Superior Mechanical and Electrical Properties of Nanocrystalline Tungsten‐Molybdenum Thin Films

Abstract: The authors report on the design and stabilization of the mechanically hard and electrically resistive b-phase W-Mo nanocrystalline thin films at room-temperature (RT). The W-Mo films are deposited under different deposition temperatures in the range of T s ¼ RT-30 C. Structural analyses indicate that, as deposited at RT, the W-Mo films crystallize in the metastable b-phase, while those deposited at higher T s (100-300 C) exhibit the thermodynamically stable a-phase. The phase-effect is significant on the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The correct description of the structure hierarchy means that the developed potential can be suitable for studying the stabilization of the A15 phase for RAs in the form of thin films [63,64,65]. Among the other potentials, tab-GAP predicts A15 to be more stable than the bcc phase for Nb, while the A15 phase was predicted to be most stable for all tested metals when using the MEAM potential.…”
Section: Bulk Properties and Point Defectsmentioning
confidence: 99%
“…The correct description of the structure hierarchy means that the developed potential can be suitable for studying the stabilization of the A15 phase for RAs in the form of thin films [63,64,65]. Among the other potentials, tab-GAP predicts A15 to be more stable than the bcc phase for Nb, while the A15 phase was predicted to be most stable for all tested metals when using the MEAM potential.…”
Section: Bulk Properties and Point Defectsmentioning
confidence: 99%
“…Also, investigations on alloyed W and Mo thin films have shown that an ideal contact electrode is viable for advanced electronic devices. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…Also, investigations on alloyed W and Mo thin films have shown that an ideal contact electrode is viable for advanced electronic devices. [17] High-quality Mo thin films are often deposited using radio frequency (RF) or direct current (DC) magnetron sputtering methods. It is well established that controlling of various sputtering…”
mentioning
confidence: 99%
“…With continuous miniaturization of electronic, optoelectronic, photonic, and spintronic devices, the low-dimensional superconducting interconnects have become the center of interest for various overlapping multidimensional research activities. Moreover, understanding and tailoring the phase formation, chemical stability, nanomechanical behavior, and optical properties of such refractory metal and the corresponding oxides are immensely important to demonstrate state-of-the-art technologies for futuristic applications. An abrupt heteroepitaxial interface with the lowest possible defect formation, absence of anisotropic conductivity through different crystal orientation, less surface scattering, and lower value of bulk resistivity-mean free path product (ρ 0 λ) has already proven to be the most desired characteristics of Nb as a superior superconducting material. ,, The journey of Nb as a superconducting charge carrier is relatively short. Highly sophisticated layer-by-layer epitaxial growth processes have demonstrated the existence of a sharp Nb–semiconductor junction. , In addition, a low-cost sputtering technique has also been certified as a potential deposition technique with a similar outcome. ,, However, optimization of growth conditions on various crystalline substrates is still considered as an open problem for further improvement.…”
Section: Introductionmentioning
confidence: 99%